EDUKASI MENGENAI PEMANFAATAN MEDIA SOSIAL DALAM PUBLIC SPEAKING BAGI SISWA/I SMK KARYA NASIONAL, KAB. KUNINGAN JAWA BARAT - Widiarti Lestariningsih; Dea Arsyad; T. Yoanyta Octora; Eti Jumiati; Asep Solihin (JURNAL ABDIMAS PLJ, 2024)
This research activity is to determin the impat of using social media in public speaking activities forr students at SMK Karya National. The times have entered the digital era where technology continues to develop rapidly and everyone is involved in the dynamics of social media. This research aims to provide education about social media in depth, both in terms of positive and negative azpects of public speaking sklills. Where currently social media is very common for everyone. Social media is also able to influence speaking style, grammar and word use. The influence of informal language and casual communication styles common on social media can be a challenge in formal communication. The significance of public speaking in the educational and professional world is crucial, students are faced with the challenge of developing public speaking skills along with the dominance of social media